Desain dan Implementasi Sistem Pendingin Berbasis Peltier TEC 12706 dengan Pemantauan Jarak Jauh Melalui Aplikasi Blynk pada Smartphone - Puspita, Nabilla Putri; Yusfi, Meqorry (Jurnal Fisika Unand, 2025)
Cooling technology plays an important role in daily life, particularly in refrigerators used for storing fruits, vegetables, and beverages. However, conventional cooling systems still use freon, which can damage the ozone layer. This study utilizes the Peltier Effect on the Peltier TEC 12706 module as an environmentally friendly cooling component. The DHT22 sensor is used to measure temperature and humidity, while the NodeMCU ESP8266 processes sensor data displayed through the Blynk application. Three fans are installed outside the cooling chamber to prevent the Peltier module from overheating, and one fan is placed inside the chamber for air distribution. A heatsink is used to assist in heat dissipation. Testing compared the DHT22 sensor with AZ HT-02 and FY-11, producing regression values of R² = 0.9902 for temeprature and R² = 0.9798 for humidity, indicating high accuracy. Using two Peltier TEC 12706 modules and a 12 V 30 A AC-DC adapter, the temperature in the cooling chamber with dimensions (26x17x10) cm was reduced to 19.6°C, with humidity rising to 90.1% within 2 hours. These results show that the developed cooling system can function effectively.